Brand Loyalty : Peran Amplified Viral Marketing dan Price Discount (Konsumen Rabbani Mall Online bandung) - Angga, Angga Risti (Service Management Triangle: Jurnal Manajemen Jasa, 2025)
Brand Loyalty is a strong commitment to buy back or continue to use a product or service you prefer consistently in the future. This research was conducted to find out the impact of Amplified Viral Marketing and Price Discount on Brand Loyalty with Rabbani Mall Online Consumer Case Study Kota Bandung. This research is descriptive and verification research using a quantitative approach. A tool for data processing using SPSS version 26. The analytical method used is double regression analysis. The results of the research show that partially Amplified viral marketing has a positive and significant influence on brand loyalty, price discount has a negative and significant effect on brand loyalties. Simultaneously, amplified Viral marketing and price discounts together have a significant and positive impact on the brand loyality on consumers Rabbani Mall Online Kota Bandung.